Environmental impact assessment of hydrogen-based auxiliary power system onboard - UYAR, TANAY SIDKI (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
The maritime transportation sector globally depends on fossil resources while this option is both diminishing and causing serious environmental and air pollution issues. Recently, hydrogen energy becomes one of the key alternatives addressing these concerns under the increasing press effect of the international community. The use of hydrogen as an energy source in ships is provided by fuel cell technologies. Although there are many types of fuel cells, Proton Exchange Membrane Fuel Cell (PEMFC) is the most widely used fuel cell type in themaritime industry. Themost important handicap for the use of hydrogen in ships seems to be the production and storage of it. For this reason, fuel cell technology and hydrogen production and storage systems must be developed in order to use hydrogenas themain propulsionsystem inlong-distance transportation in themaritime sector. In this study, Reference Energy System (RES) is established for a chemical tanker ship to determine the current energy flow from various resources to demands. Then the appropriate parameters are assigned and this framework is specified by the respective data. Following this phase; the current situation has been developed as the base scenario and analyzed by using the Low Emission Analysis Programme (LEAP) energy modeling platform. Additionally, two alternative scenarios including the hydrogen-based have been applied against the base scenario to compare the environmental results in the 2017-2050 time period. When the results are evaluated, it is predicted that although it is not sufficient for IMO and EMSA targets, implementation of hydrogen contributes to the carbon emission reduction positively and it will be more beneficial to apply to the main drive system with the technological developments to be made in the near future. (C) 2021 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: LEAP; Reference energy system; Hydrogen; Ship energy system modeling; Ship energy system analysis; FUEL-CELLS; ELECTRICITY; DEMAND